STRATEGIES TO ADDRESS ACADEMIC ABSCONDMENT IN NIGERIAN TERTIART INSTITUTIONS - Ogunode, Niyi Jacob; Nwisagbo, Ayodele Ebunolu; Bamson, Tamunomiebi (Journal of Innovation in Education and Social Research, 2026)
The paper explores different strategies that can be adopted and deployed to address the problems of academic abscondment in the Nigerian tertiary institutions. The paper employed the used of secondary data. The various data were collected through print resources and online publications. The paper find out that strengthening bond agreements and legal enforcement, establishing effective monitoring and tracking mechanisms, providing incentives and attractive working conditions, strengthening institutional accountability, promoting national loyalty and ethical orientation, bilateral agreements with host countries and universities, establishing a centralized database and sanction mechanism and strengthening post-return reintegration and career development are some of thestrategies that can be adopted and be deployed to address the problems of academic abscondment in the Nigerian tertiary institutions.Based on these strategies identified, the paper hereby recommend that the Federal Ministry of education and Tertiary Education Trust Fund (TETFund) should adopt the various strategies and combine them with a multi-dimensional approach such as enforcement, motivation, and systemic reform. By ensuring strict compliance with sponsorship agreements, improving working conditions, fostering patriotism, and enhancing institutional accountability, Nigeria can minimize brain drain and fully realize the objectives of TETFund’s human capacity development initiatives.